Synthesis of Potential Mycobacterium Tuberculosis InhA Inhibitors - Saleem, Tabrez Ali (2023)
Tuberculosis caused by Mycobacterium tuberculosis is an infectious disease that predominately affects the lungs. Mycobacterium tuberculosis can be prevented or treated by many anti-tuberculosis drugs. Isoniazid 1 is a prodrug that is used in the treatment against Mycobacterium tuberculosis and for isoniazid 1 to become potent it requires to be activated by KatG prior to forming the isoniazid-NAD+ adduct. However, mutations within the KatG peroxidase results in the resistance of the major antituberculosis drugs, isoniazid 1 and ethionamide 7.